Surgical quality assurance in head and neck cancer trials: an EORTC Head and Neck Cancer Group position paper based on the EORTC 1420 'Best of' and 24954 'larynx preservation' study. (November 2018) - Simon, Christian; Caballero, Carmela; Gregoire, Vincent; Thurnher, Dietmar; Koivunen, Petri; Ceruse, Philippe; Spriano, Giuseppe; Nicolai, Piero; Licitra, Lisa; Machiels, Jean-Pascal; Hamoir, Marc; Andry, Guy; et al.
Abstract: Quality improvement of care for patients with head and neck cancer remains a constant objective for the multidisciplinary team of physicians managing these patients. The purpose of quality assurance (QA) for head and neck surgical oncology and surgical trials however differs. While QA for the general head and neck patient aims to improve global outcome through structural changes of health-care systems, QA for surgical trials pursues the goal to help providing meaningful results from a clinical trial through the definition of structure, process and outcome measures within the trial. Establishing a QA program for surgical trials is challenging largely due to the variation in the execution of surgical techniques. Within this article, we describe the surgical QA program, which was developed for the phase III European Organisation for Research and Treatment of Cancer (EORTC) 1420 study, a trial assessing swallowing function after transoral surgery compared with radiation therapy. We propose based on our experience to further develop surgical QA for surgical clinical trials by introducing two separate components, one adaptable and one non-adaptable. The adaptable is tailored to the scientific question and specific procedure; the non-adaptable consists of minimal structural requirements of the clinical unit to participate in surgical trials at EORTC as well as guidelines and incentives for protocol adherence based on our experience in EORTC 24954. Finally, we strongly believe that surgical QA designed for clinical trials may serve as a basis for the development of QA surgical guidelines in clinical practice. Highlights: Quality assurance (QA) programs for surgical trials are challenging. We propose a QA framework consisting of an adaptable and a non-adaptable component. The adaptable is tailored to the scientific question and specific procedure. The non-adaptable consists of minimal structural requirements of the clinical unit. Surgical QA within clinical trials may serve as the basis for guidelines in clinical practice.